2021
DOI: 10.1186/s12886-021-02032-z
|View full text |Cite
|
Sign up to set email alerts
|

PreserFlo MicroShunt® exposure: a case series

Abstract: Background PreserFlo® MicroShunt (PM) (also known as InnFocus® MicroShunt) is a subconjunctival stent implanted ab externo via a minimally invasive surgical procedure. The current indication is progressive, mild to moderate, open angle glaucoma uncontrolled on topical medications. According to the literature, adverse events are rare, mild and transient. Case presentation Two cases of stand-alone PreserFlo MicroShunt® implantation in patients with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
(45 reference statements)
0
12
1
3
Order By: Relevance
“…Thus, the Preserflo MicroShunt, a minimally invasive glaucoma surgery device, has a good efficacy and safety profile as compared to other MIGS [ 23 , 24 , 25 , 26 ]. In contrast to the study of Bunod et al [ 27 ], we did not observe any cases of tube exposure in our research.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the Preserflo MicroShunt, a minimally invasive glaucoma surgery device, has a good efficacy and safety profile as compared to other MIGS [ 23 , 24 , 25 , 26 ]. In contrast to the study of Bunod et al [ 27 ], we did not observe any cases of tube exposure in our research.…”
Section: Discussioncontrasting
confidence: 99%
“…The approach has been recommended by another group in the context of deficient tenon's capsule (discussed in more detail below). 7 It is not clear at this point whether the inclusion of a nylon suture provides additional benefit. However, we have not had other similar suture related issues and we continue to incorporate its use with MicroShunt procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent series of 2 cases of MicroShunt exposure cited severe blepharitis associated with ocular surface inflammation and deficiency in tenons capsule as common features between them. 7 One of the patients had undergone a non-penetrating deep sclerectomy in both eyes 5 years prior. In situations where there is a deficiency of tenon's capsule, the authors recommend use of a 10-0 nylon suture to fix the distal part of the MicroShunt to the sclera, in a similar manner to which we have described.…”
Section: Discussionmentioning
confidence: 99%
“…The safety profile of the PreserFlo MicroShunt was confirmed to be excellent in recent years, with only a few cases of sight-threatening adverse effects described in the literature. Bunod et al described two cases of PreserFlo exposure, which required device removal, in eyes with pre-existing blepharitis and the lack of a Tenon’s flap [ 59 ]. This potentially vision-threatening complication, because of the risk of endophthalmitis, suggested that ocular surface inflammation should be detected and treated prior to device implantation [ 59 ].…”
Section: Adverse Effects Of Preserflo Microshuntmentioning
confidence: 99%
“…Bunod et al described two cases of PreserFlo exposure, which required device removal, in eyes with pre-existing blepharitis and the lack of a Tenon’s flap [ 59 ]. This potentially vision-threatening complication, because of the risk of endophthalmitis, suggested that ocular surface inflammation should be detected and treated prior to device implantation [ 59 ]. The risk of endophthalmitis after PreserFlo implant surgery remains unclear, with only Brambati et al reporting a case of ocular infection following post-operative needling procedures, managed with therapeutic pars plana vitrectomy (PPV) and antibiotics injection [ 54 ].…”
Section: Adverse Effects Of Preserflo Microshuntmentioning
confidence: 99%